The downside effect of emotional intelligence on job stress among non-academic university staff - Kamarozaman, Nur Elina; Ma’rof, Aini Azeqa; Hamsan, Hanina Halimatusaadiah; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2022)
Behavioral science researchers and scholars have attempted to find effective elements that influence efficiency and effectiveness to improve organizational performance, as well as factors that contribute to job stress. Meanwhile, previous studies shows that by enhancing emotional intelligence, it can help individual to cope with stress, develop great relationships, empathize with others, and accomplish goals. Thus, this study aimed to examine the relationship between four types of emotional intelligence: self-emotion appraisal, other’s emotion appraisal, use of emotions, and regulation of emotion on job stress. A cross-sectional design method was used to employ a quantitative approach via a self-administered questionnaire with respondents were among the non-academic staff from a Malaysian public university. Interestingly, the results contradict to previous studies whereby all four types of emotional intelligence were positively associated to job stress with regulation of emotion being the main unique predictor to job stress. Specifically, the results indicate that the higher the individual’s emotional intelligence, the more prone they were to job stress. Thus, further explanation and implications of high emotional intelligence to one’s functioning has been discussed in this paper.